Shamanic practices in the belief system of the Kazakhs and Tuvans, 1920s-1960s: A comparative analysis - Dosmurzinov, Rustem K. (The New Research of Tuva, 2023)
The article highlights the general and distinctive characteristics of shamanic practices among the Kazakh and Tuvan peoples. They were captured in the remaining traditional forms of the early 20th century. The source base of the research includes the publications by F. A. Fielstrup (1920s), F. Ya. Kon (1930s) and M. B. Kenin-Lopsan (the first half of the 20th century). The starting point for comparison was the assumption that, due to the longer preservation of the traditional way of life and beliefs, more archaic shamanic ideas and practices became permanent and continued to develop in Tuvan shamanism rather than in Kazakh shamanism. The comparison of the data showed that: firstly, the structure of shamanic practices of Kazakh and Tuvan shamans is almost identical, including such stages as preparation of the shaman for the kamlanie (shamanistic ritual), the kamlanie that mostly consists of reciting prayers and incantations and completion of this ritual; secondly, traditional methods of treatment are the most important part of shamanic practices of both Kazakh and Tuvan shamans. The proposed hypothesis of the research has been only partially confirmed: despite the earlier development of modernization processes, as well as the influence of the Islamic doctrine, archaic beliefs and elements that find parallels in the Shamanism of the Tuvans have also remained in Kazakh shamanic practices.